Brain neuronal and glial damage during acute COVID-19 infection in absence of clinical neurological manifestations. Issue 12 (22nd September 2022) - Plantone, Domenico; Locci, Sara; Bergantini, Laura; Manco, Carlo; Cortese, Rosa; Meocci, Martina; Cavallaro, Dalila; d'Alessandro, Miriana; Bargagli, Elena; De Stefano, Nicola
Abstract : Background: To assess whether SARS-CoV-2 infection may affect the central nervous system, specifically neurons and glia cells, even without clinical neurological involvement. Methods: In this single centre prospective study, serum levels of neurofilament light chain (sNfL) and glial fibrillar acidic protein (sGFAp) were assessed using SimoaTM assay Neurology 2-Plex B Assay Kit, in 148 hospitalised patients with COVID-19 without clinical neurological manifestations and compared them to 53 patients with interstitial pulmonary fibrosis (IPF) and 108 healthy controls (HCs). Results: Age and sex-corrected sNfL levels were higher in patients with COVID-19 (median log10-sNfL 1.41; IQR 1.04–1.83) than patients with IPF (median log10-sNfL 1.18; IQR 0.98–1.38; p<0.001) and HCs (median log10-sNfL 0.89; IQR 0.72–1.14; p<0.001). Likewise, age and sex-corrected sGFAP levels were higher in patients with COVID-19 (median log10-sGFAP 2.26; IQR 2.02–2.53) in comparison with patients with IPF (median log10-sGFAP 2.15; IQR 1.94–2.30; p<0.001) and HCs (median log10-sGFAP 1.87; IQR 0.64–2.09; p<0.001). No significant difference was found between patients with HCs and IPF (p=0.388 for sNfL and p=0.251 for sGFAp). In patients with COVID-19, a prognostic model with mortality as dependent variable (26/148 patients died during hospitalisation) and sNfl, sGFAp and age as independent variables, showed an area under curve of 0.72 (95% CI 0.59 to 0.84; negative predictive value (NPV) (%):80, positive predictive value (PPV)(%): 84; p=0.0008). Conclusion: The results of our study suggest that neuronal and glial degeneration can occur in patients with COVID-19 regardless of overt clinical neurological manifestations. With age, levels of sNfl and GFAp can predict in-hospital COVID-19-associated mortality and might be useful to assess COVID-19 patient prognostic profile.